Case reportTransient thyrotoxicosis following prolonged use of gonadotropin-releasing hormone agonist in women with endometriosis – a case report - Nakashima, Akira; Nakagawa, Koji; Ohgi, Shirei; Horikawa, Takashi; Kamura, Toshiharu; Saito, Hidekazu (Archives of Medical Science, 2008)
This paper reports two cases showing transient thyrotoxicosis caused by prolonged use of gonadotropin-releasing hormone (GnRH) agonist. Case 1, a 31-year-old woman, was administered GnRH-agonist (leuprorelin acetate) for treatment of endometriosis. After four months she showed thyroid dysfunction. Case 2, a 43-year-old woman, who was previously diagnosed with chronic thyroiditis, was treated with GnRH-agonist (nafarelin acetate) for her endometriosis. Five months later, her thyroid functions worsened. After discontinuation of the GnRH-agonist, thyroid function of both cases recovered. In selected patients, who are on GnRH-agonist, attention to thyroid function is important.